Ertapenem prophylaxis reduces sepsis after transrectal biopsy of the prostate. (March 2014) - Losco, Giovanni; Studd, Rod; Blackmore, Timothy
Abstract : Objective: To prospectively trial ertapenem prophylaxis in patients with known risk factors of sepsis undergoing transrectal biopsy of the prostate. Patients and Methods: In this prospective audit, patients were identified as having a low‐ or high‐risk of sepsis based on a questionnaire about established risk factors: previous biopsy; recurrent urine infections; receiving ciprofloxacin in the 12 months prior; travel to South‐East Asia or South America in the previous 6 months; or diabetes, immune system impairment or receipt of immunosuppressant drugs. All received ciprofloxacin and amoxicillin‐clavulanate and high‐risk patients additionally received ertapenem. Sepsis requiring hospital admission was recorded. Data was analysed using a two‐tailed Fisher's exact test. Results: In all, 80 men were identified as high risk of sepsis and 90 as low risk during the audit period. Six patients in the low‐risk group (6.7%, 95% confidence interval 2.1–11.3) and none in the high‐risk group developed sepsis ( P = 0.03). Of the six developing sepsis, two grew ciprofloxacin‐resistant organisms, two had no growth and two grew a ciprofloxacin‐sensitive organism, although one of these grew extended‐spectrum β‐lactamase‐producing Escherichia coli. Conclusion: The addition of ertapenem to standard prophylaxis is effective at reducing sepsis after prostate biopsy. Risk stratification is not effective at identifying those men at low risk of sepsis, as these men still have a high sepsis rate. Ertapenem prophylaxis for all patients undergoing prostate biopsy is likely to be the most effective strategy in our population group.